ANALISIS INKLUSI KEUANGAN MELALUI ELEKTRONIK WARUNG GOTONG ROYONG (E-WARONG) PADA MASA PANDEMI - Hermeindito, Andreas; Susilo (Contemporary Studies in Economic, Finance and Banking, 2022)
The low financial inclusion index in Indonesia compared to ASEAN countries needs to be improved through BSNT.This research aims to determine the understanding, experience, form of service and the tendency of non-cash transactions of BSNT recipients in Kediri City & Regency.This research uses a descriptive quantitative method with a percentage descriptive analysis technique. Data are obtained through interviews, documentation and observation. Respondents to the study were BSNT recipients and owners of E-Warong.Research sampling using purposive sampling. The results of this study show that most of the BSNT recipients understand and are ready to use cashless transaction services in BSNT distribution.However, BSNT recipients still do not optimize and do not know the type of electronic money service.Respondents who own E-warong provide various types of payments and financial service facilities.The trend of non-cash transactions has increased after being equipped with cashless payment facilities on E-Warong.Efforts to increase financial inclusion through E-Warong in BSNT distribution are able to bring BSNT recipients in Kediri City and Regency to get to know and use financial services